Janitors, street vendors, and activists : the lives of Mexican immigrants in Silicon Valley - Zlolniski, Christian (University of California Press, 2006)
This highly accessible, engagingly written book exposes the underbelly of California's Silicon Valley, the most successful high-technology region in the world, in a vivid ethnographic study of Mexican immigrants employed in Silicon Valley's low-wage jobs.